Preliminary study of novel, timed walking tests for children with spina bifida or cerebral palsy. (8th July 2016) - Kane, Kyra J; Lanovaz, Joel; Bisaro, Derek; Oates, Alison; Musselman, Kristin E
Objective: Walking assessment is an important aspect of rehabilitation practice; yet, clinicians have few psychometrically sound options for evaluating walking in highly ambulatory children. The purpose of this study was to evaluate the validity and reliability of two new measures of walking function—the Obstacles and Curb tests—relative to the 10-Meter Walk test and Timed Up and Go test in children with spina bifida or cerebral palsy. Methods: A total of 16 ambulatory children with spina bifida ( n =9) or cerebral palsy ( n =7) (9 boys; mean age 7years, 7months; standard deviation 3years, 4months) and 16 age- and gender-matched typically developing children participated. Children completed the walking tests, at both self-selected and fast speeds, twice. To evaluate discriminative validity, scores were compared between typically developing and spina bifida/cerebral palsy groups. Within the spina bifida/cerebral palsy group, inter-test correlations evaluated convergent validity and intraclass correlation coefficients evaluated within-session test–retest reliability. Results: At fast speeds, all tests showed discriminative validity ( p <0.006 for typically developing and spina bifida/cerebral palsy comparisons) and convergent validity ( rho =0.81–0.90, p ⩽0.001, for inter-test correlations). At self-selected speeds, only the Obstacles test discriminated between groups ( p =0.001). Moderately strong correlations ( rho =0.73–0.78, p ⩽0.001) were seen between the 10-Meter Walk test, Curb test, and Timed Up and Go test. Intraclass correlation coefficients ranged from 0.81 to 0.97, with higher test–retest reliability for tests performed at fast speeds rather than self-selected speeds. Conclusion: The Obstacles and Curb tests are promising measures for assessing walking in this population. Performing tests at fast walking speeds may improve their validity and test–retest reliability for children with spina bifida/cerebral palsy.